Lower experience increases concussion susceptibility in Brazilian jiu-jitsu practitioners - dos Santos, Marco Antonio Ferreira (2022)
The present study is a descriptive-documental study that evaluates a survey database about Brazilian Jiu-Jitsu (BJJ) practitioners and concussions. We investigate any relationship between lifetime practice and the incidence of concussions in adults. For this, an online survey composed of 17 questions was sent to 42 BJJ coaches. The Survey Monkey platform was used to host the survey. Some demographic data was collected, followed by questions related to the BJJ practice. A total of 791 practitioners had completed or partially answered the survey. The results show that concussions are more frequent at the beginner's white 49.0% and blue belt 33.3% (p≤ 0.01). The symptom "seeing stars" showed a positive and significant correlation (r= 0.169, p≤ 0.002) with a white and blue belt. After a concussion, white and blue belts return faster than the others (χ2= 190.964; p≤ 0.01). White, blue, and purple belts are the least likely to seek medical care after a concussion (χ2= 14.874; p≤ 0.01). Together, our results showed the need for an educational intervention with the BJJ coaches and beginners regarding awareness about concussions and possible post-traumatic issues and creating procedures to deal with concussions in BJJ.